2014
DOI: 10.2215/cjn.03370414
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron Exposure and Mortality in Patients on Hemodialysis

Abstract: Background and objectives Clinical trials assessing effects of larger cumulative iron exposure with outcomes are lacking, and observational studies have been limited by assessment of short-term exposure only and/or failure to assess cause-specific mortality. The associations between short-and long-term iron exposure on all-cause and cause-specific mortality were examined.Design, setting, participants, & measurements The study included 14,078 United States patients on dialysis initiating dialysis between 2003 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…The study by Miskulin et al (14) also raises concern with respect to intravenous iron and infection. Iron is a key nutrient for microorganisms.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Miskulin et al (14) also raises concern with respect to intravenous iron and infection. Iron is a key nutrient for microorganisms.…”
mentioning
confidence: 99%
“…A relatively underpowered study of Taiwanese patients on dialysis found that intravenous iron doses .800 mg over 6 months were associated with a higher risk of mortality compared with lower doses (13). In this issue of CJASN, Miskulin et al (14) report on patients on hemodialysis treated at Dialysis Clinic Inc. facilities. The study used robust statistical methods to account for time-varying confounding (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Data from epidemiological studies [65][66][67][68]. On the contrary, three other epidemiological studies with longer follow-up (1 to 2 years) showed that excessive IV iron might be associated with increased mortality and cardiovascular events in hemodialysis patients [12][13][14].…”
Section: Potential Morbidity and Mortality Related To Iron Overuse Inmentioning
confidence: 98%